The Fall of Babylon - Griffith, D. W.; Bitzer, Gottfried W.; Talmadge, Constance; Marshall, Tully; Paget, Alfred (The Masters of Cinema Series, 2014)
After D.W. Griffith's masterpiece "Intolerance" failed at the box office, two of the four tales that make up that movie were extracted and released as their own separate features to try to recoup more money. "The Fall of Babylon" is the best and most lavish of the four, featuring a set larger than any previously built for a film, 5000 extras, and 250 chariots. The battle scenes are large and sweeping, with some surprisingly violent stunts and effects, yet for all the spectacle, Griffith keeps the essence of the story centered on basically just one character, called only the Mountain Girl, who is instrumental in bringing about the events that come to pass. Her story is given as much attention as Babylon's. It's a wonderful perspective; in rooting a historical saga with a human element, it reminds us that humanity and history are not as segregated as we sometimes inexplicably think. The story stands alone well enough, but it is best to see it as it was intended to be, within the larger framework of "Intolerance". There, the impact of this story is all the greater, as it represents one of several facets of a great human injustice. [www.rinkworks.com]